MORPHOLOGICAL , BIOCHEMICAL AND GROWTH CHARACTERISTICS OF SERRATIA STRAINS ISOLATED FROM SARDINE (SARD!NELLA LONGICEPS) - NAMBIAR, V NARAYANAN; SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2017)
Two aerobic, gram-negative asporogenous, red-pigmented"rod-shaped bacterial strains were isolated from oil sardine( Sardinella longiceps). Their morphological, biochemical andgrowth characteristics are reported. The pigment was identifiedto be a prodigiosene. The strains were found to resembleSerratia plynmthica. Effect of temperature and certain carbohydrateson pigmentation was also studied. Iron was found toinhibit pigmentation, and mannitol or sorbitol removed s.uchinhibition.